Role of The behaviors of administrative leadership in achieving organizational excellence A field research in a sample of the Iraqi private banks - ناظم جواد عبد سلمان الزيدي; علي عبد الأمير عبد الحسين كمونه (Iraqi Journal for Administrative Sciences, 2024)
The research topic tackled the behaviors of administrative leadership and its role in achieving organizational excellence, Given the importance of the private banking sector and its impact on the country’s economy has research was conducted in the (12) banks of the Iraqi private banks were randomly selected, And applied the research on a sample of 120 people from the leaders in the surveyed banks (commissioners managers and branch managers, assistants of managers, and heads of departments). Find the questionnaire as a tool to get of data and information has been adopted as well as personal interviews conducted by the researcher with a number of leaders of the surveyed banks. and sought search to achieve a set of goals, most notably : 1- Prepare of philosophical and theoretical framework based on rooting intellectual and make a modest contribution with respect to variables and dimensions of the current research, which are needed to enrich the conceptual and theoretical widely in order to benefit from the philosophical and intellectual data upon which the setting. 2- know extent interesting the surveyed banks concepts of managerial leadership behaviors and strategies of knowledge management and organizational excellence. The final result of this research is a set of conclusions of the most important are: (banks researched interest of all the variables and dimensions of search, having influence relations of behaviors of administrative leadership in achieving organizational excellence), he research also included a set of recommendations including (The focus on the behaviors of administrative leadership in the surveyed banks due to their moral impact in achieving organizational excellence, The importance of conducting benchmarks between the surveyed banks and international banks in order to know the most important global developments in the field of banking and knowledge of the most influential behaviors in achieving excellence.